CEREBRAL VISUAL MPAIRMENT: STRATEGI AND ACTIVITY (Annual of the Faculty of Philosophy in Skopje, 2015)
According to the latest research, Cerebral Visual Impairment (CVI) is one of the most common reasons for visual impairment. There are many definitions of CVI, and common for all of them is that "the eyes are good, but the brain is not", i.e. The functioning of sense of sight is fine, but it’s not a case with brain area which is responsible for the interpretation of visual information. The aim of this paper is to present the characteristics of children with CVI, and the strategies and activities used for treatment. CVI has a negative impact on almost all developmental domains, motor skills, cognitive skills, and social skills. At children with CVI, identification, assessment and careful planning of the intervention and treatment may facilitate their visual function, and thus the ability to read and learn. In particular, with systematic and targeted strategies and activities, children with CVI can have a significant and stable progress in the use of there sight.
Keywords: CORTICAL VISUAL IMPAIRMENT; VISUAL FUNCTIONING; STRATEGY